SELECTION OF DECOMMISSIONING METHODS FOR GAS PLANT FACILITIES USINGANALYTICAL NETWORK PROCESS - Prayudha, Aditya; Buda Artana, Ketut; Pratiwi, Emmy; C Katon, Yoke; Agung P, Achmad (Journal of Marine-Earth Science and Technology, 2021)
The high complexity of decommissioning decisions presents a challenging problem for decision-makers due to the various parameters and stakeholders involved. Currently, a Floating Production Unit, BW Joko Tole located at the Lapangan Terang Sirasun Batur field, in East Madura Waters are expected to be decommissioned as gas reserves are running low for the upcoming 9 years. Multi-Criteria Decision Analysis has begun to be implemented by several oil and gas companies and several studies applied various MCDA methods in choosing the best alternatives. Analytical Network Process is a powerful tool to handle the interdependencies of elements involved in decommissioning, as no other MCDA methods can accommodate these relationships between elements. This study aims to simulate the implementation of the Analytical Network Process as one of MCDA methods in choosing decommissioning methods for these facilities, specifically pipelines and umbilicals operated by FPU BW Joko Tole. Regulatory review is carried out to determine the suitable alternatives, criteria, and sub-criteria needed to be considered in choosing decommissioning alternatives and evaluated using the Analytical Network Process (ANP). This study will provide an example of the ANP network model in decommissioning decisions followed by a sensitivity analysis to determine the robustness of the chosen alternatives and the values of each element involved.